Policy Failure in the Triangle of Growth: Labour Market, Human Capital, and Innovation in Spain and Italy. Issue 1 (2nd January 2019) - Burroni, Luigi; Gherardini, Alberto; Scalise, Gemma
ABSTRACT: This article focuses on the Italian and Spanish models of growth and analyses labour market, human capital and innovation policy reforms since the mid 1990s. The comparison with France and Germany shows the constraints that have hindered the rise of institutional complementarities and the competitiveness of the two Mediterranean countries already before the introd uction of the euro and the outbreak of the 2008 crisis. The analysis highlights both similarities and structural differences between Italy and Spain and demonstrates the long-term institutional conditions that explain why the economic breakdown has had such a deep impact on the two countries.